2021
DOI: 10.3389/fphar.2021.661853
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Inhibits Intestinal Epithelial Cell Apoptosis Through the Unfolded Protein Response Pathway in Ulcerative Colitis

Abstract: Ulcerative colitis (UC) is a type of inflammatory bowel disease (IBD) that occurs in the lining of the rectum and colon. Apoptosis of the intestinal epithelial cells (IECs) is common in active UC patients. Ghrelin is reported to be downregulated in apoptosis of IECs induced by tumor necrosis factor-α (TNF-α). Therefore, we hypothesized that ghrelin might play an antiapoptotic role in UC progression, which was investigated using in vitro and in vivo studies. The TNF-α-treated Caco-2 cell model and mouse colitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…In addition, Cheng et al [ 145 ] reported that ghrelin prevented the breakdown of intestinal barrier function in DSS-induced colitis by inhibiting the activation of nuclear factor kappa B (NFκB). This observation is supported by the findings of Zhang et al [ 139 ], which show that the beneficial effect of ghrelin in DSS-induce colitis involves the inhibition of intestinal cell apoptosis.…”
Section: Protective Anti-inflammatory and Healing Effects Of Ghrelin In The Digestive Systemsupporting
confidence: 82%
See 2 more Smart Citations
“…In addition, Cheng et al [ 145 ] reported that ghrelin prevented the breakdown of intestinal barrier function in DSS-induced colitis by inhibiting the activation of nuclear factor kappa B (NFκB). This observation is supported by the findings of Zhang et al [ 139 ], which show that the beneficial effect of ghrelin in DSS-induce colitis involves the inhibition of intestinal cell apoptosis.…”
Section: Protective Anti-inflammatory and Healing Effects Of Ghrelin In The Digestive Systemsupporting
confidence: 82%
“…These findings suggest that endogenous ghrelin may protect and accelerate the healing of inflamed colonic mucosa, and that ghrelin could be useful in the treatment of ulcerative colitis [137]. The therapeutic effect of ghrelin in TNBS-induced colitis was also shown by Zhang et al [139].…”
Section: The Large Bowelmentioning
confidence: 80%
See 1 more Smart Citation
“…IBD patients, especially UC patients, have high circulating ghrelin [24], and exogenous ghrelin administration has been shown to aggravate experimental colitis [25]. At the same time, other studies showed that ghrelin protects against tissue damage in ulcerative colitis by inhibiting apoptosis of intestinal epithelial cells [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, apoptosis regulates the replacement rate of the epithelial cells, and an increase in epithelial cell apoptosis in colitis disrupts the mucosal epithelial barrier ( Cai et al, 2018 ; Xiong et al, 2019 ). However, an aberrantly high rate of IEC apoptosis in IBD leads to a positive feedback cycle of epithelial barrier disruption but does not cause an inflammation response ( Bayrer et al, 2018 ; Zhang L. et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%